Securing Communication Networks at the Physical Layer: A DRL and Phase Optimization Approach - Kamal, Mian Muhammad; Abideen, Syed Zain Ul; Sharafian, Amin; Ibrahim, Anwar Hassan; Islam, Muhammad; Habib, Shabana (IET signal processing, 2025)
Securing communication between multiple users efficiently while there are too many potential eavesdroppers has become an important issue with the rise of the Internet of Things (IoTs). This paper extends on earlier research, moving from a single‐user and single‐eavesdropper scenario to a complex multiuser and multieavesdropper context, and incorporates an advanced physical layer security (PLS) technique for the first time. Using reconfigurable intelligent surfaces (RISs) enhances the strength and quality of signals for intended users, while those to the unintended users are suppressed. Real‐time control of the RIS phase shifts is enabled through a deep deterministic policy gradient (DDPG) algorithm and this control significantly changes the trade‐off between security and energy wastage. The simulation results demonstrate that the developed approach can scale up in densely populated urban centers, while increasing the bit error rate (BER) performance and the overall energy efficiency across different wireless mobile channels.